2014
DOI: 10.3389/fncel.2014.00316
|View full text |Cite
|
Sign up to set email alerts
|

Use of induced pluripotent stem cell derived neurons engineered to express BDNF for modulation of stressor related pathology

Abstract: Combined cell and gene-based therapeutic strategies offer potential in the treatment of neurodegenerative and psychiatric conditions that have been associated with structural brain disturbances. In the present investigation, we used a novel virus-free re-programming method to generate induced pluripotent stem cells (iPSCs), and then subsequently transformed these cells into neural cells which over-expressed brain derived neurotrophic factor (BDNF). Importantly, the infusion of iPSC derived neural cells (as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Levels of norepinephrine (NE), serotonin (5-HT) and dopamine (DA), and their respective primary metabolites, 3-methoxy-4-hydroxyphenylglycol (MHPG), 5-hydroxyindole acetic acid (5-HIAA), and 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), were determined by HPLC within relevant brain punches according to previously reported methods ( Liu et al, 2014 ). Tissue punches were homogenized by ultrasonic disruption (Sonic Dismembrator Model 100, Fisher Scientific) in the homogenizing solution in which they were initially frozen (with DHBA as an internal standard).…”
Section: Methodsmentioning
confidence: 99%
“…Levels of norepinephrine (NE), serotonin (5-HT) and dopamine (DA), and their respective primary metabolites, 3-methoxy-4-hydroxyphenylglycol (MHPG), 5-hydroxyindole acetic acid (5-HIAA), and 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), were determined by HPLC within relevant brain punches according to previously reported methods ( Liu et al, 2014 ). Tissue punches were homogenized by ultrasonic disruption (Sonic Dismembrator Model 100, Fisher Scientific) in the homogenizing solution in which they were initially frozen (with DHBA as an internal standard).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, mice which were exposed to a stressor regimen and received BDNF-secreting iPSC-derived neural progenitors via intracerebroventricular transplantation reversed the impact of stressor challenge by subventricular zone adult neurogenesis [112].…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 94%
“…In another significant study, Cho, Hunter, Ye, Pongos, and Chan (2019b) generated transgenic HD monkey NPCs from their iPSCs and confirmed the efficacy of the combined use of the obtained NPCs and gene therapy in a transgenic HD mouse model. On the other hand, G. Liu et al (2014) found that the combination of iPSCs and trophic factors, in particular brain‐derived neurotrophic factor (BDNF), has the potential to stimulate neurogenesis and enhance preservation of neuronal structure and/or function, providing promising potential in disease‐modifying treatment of HD (G. Liu et al, 2014). According to other reports, iPSC‐derived NPCs transplantations diminished behavioral deficits and improved neuropathological variations in HD mouse models (Al‐Gharaibeh et al, 2017).…”
Section: Ipscs For Cell‐based Therapy Of Neurodegenerative Diseasesmentioning
confidence: 99%